Importance of Vitamin A in the nutrition - Koprivica, Marko M; Bjelanović, Jelena (Medicinski časopis, 2021)
Vitamin A is a group of molecules that are introduced into the body through food. This vitamin is present in food of vegetable and animal origin. Daily vitamin A needs depend on age and reproductive status. The lowest concentrations arerequired by infants and children up to 14 years of age, while pregnant women and lactating women are more likely to have the highest vitamin A needs. In the human body, vitamin A participates in numerous physiological processes. This vitamin forms the pigment rhodopsin which enables night vision. In addition to this role, vitamin A exerts its function in the immune system, where it participates in maintaining the integrity of the epithelial membranes, as well as in the proper functioning and differentiation of lymphocytes. More recent studies show that vitamin A has a protective role in the process of carcinogenesis and that its regular use prevents gastric cancer from developing. Vitamin A deficiency is a serious public health problem in certain regions of the world, so vitamin supplementation is recommended in some cases in children up to 5 years of age and in pregnant women.